Effect of castration method on stocker health and gain - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1992)
Two field trials were conducted to compare two different band-castration techniques with surgical castration of calves and yearlings. In Trial I, the bull calves were surgically castrated or banded with Elastrator® rubber rings and compared with calves purchased as steers. Purchased steers gained faster (P<.05) during the 33-day receiving trial than bulls castrated by either method, but no difference was observed in percentage of sick calves. In Trial II, yearling bulls were surgically castrated or banded with the EZE® Bloodless Castrator device. Yearlings purchased as steers gained faster (P<.05) than EZE-castrated bulls during the 110-day trial. Bulls castrated by either method required more medications (P<.07) than steers. In both trials, there was no advantage to banding compared with surgical castration of bulls in terms of gain or health.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Castration; Banding; EZE device; Stocker cattle